Oral health status of patients due to immunosuppressive therapy after organ transplantation operations - Tatyana N. Manak; Christina I. Metelitsa (LLC "MEDIAFORMAT", 2021)
Immunosuppressive therapy - therapy to suppress undesirable immune reactions of the body, is mandatory and lifelong after an organ transplantion. The risk of oral diseases increases against the background of continuous immunosuppressive therapy. The article presents the most common complications of immunosuppressive treatment in the oral cavity. These are, first of all, diseases of the oral mucosa caused by a fungal, bacterial or viral factor, such as oral hairy leukoplakia, stomatitis, erosive-ulcerative lesions, hyperkeratosis, exudative multiform erythema as well as diseases of marginal periodontium, xerostomia and dental caries. To ensure a high level of dental health after the organ transplantation operation, dispensary observation and timely diagnosis of diseases of the oral cavity are necessary.